2006
DOI: 10.1111/j.1362-1017.2006.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical assessment: whose role is it anyway?

Abstract: The increasing acuteness of care and developing technologies present new opportunities and challenges for the nursing profession. The NHS Plan emphasizes the need for change to meet these demands, especially in the area of patient assessment. Nurses are extending their repertoire of skills to include those that were once the domain of junior doctors. These new skills tend to be used mostly by experienced nurses such as the specialist or advanced nurse practitioner. One such skill is physical assessment. Tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 29 publications
0
39
0
4
Order By: Relevance
“…West [25] suggested that physical assessment to enhance safe and effective patient care must include in contemporary nursing practice. Physical assessment education has two perspectives: positivism and interpretivism.…”
Section: Introductionmentioning
confidence: 99%
“…West [25] suggested that physical assessment to enhance safe and effective patient care must include in contemporary nursing practice. Physical assessment education has two perspectives: positivism and interpretivism.…”
Section: Introductionmentioning
confidence: 99%
“…Comments included scattered complaints about inadequate pre-implementation education, suggestions that additional education about the innovation might improve patient outcomes, and strong recommendations that such education should be delivered to all nursing and medical staff on the unit. West (2006) has pointed out that education plays a pivotal role in preparing intensive care nurses to meet expanded responsibilities for patient assessment as their scope of practice evolves). However, the critical care nurses in both this study and that of Weir and O'Neill (2008) placed education in a much broader perspective when they recommended that education about practice innovation should extend beyond the boundaries of their own profession.…”
Section: Discussionmentioning
confidence: 99%
“…12 This therefore warrants the need for other timely bedside assessment to support accurate monitoring and diagnoses of respiratory dysfunction and, in turn, supports clinical decision making in real time. 13,14 Bedside respiratory assessments are most commonly performed by doctors, nursing staff, 15 physical therapists, 13 and respiratory therapists 16 to differentiate between a range of pulmonary disorders, including pulmonary edema, consolidation, atelectasis, interstitial lung disease, bronchospasm, and retained secretions. 1 One of the most common bedside respiratory assessments performed in clinical practice is lung auscultation, 1,17 which is considered an integral part of the clinical reasoning process for qualified and training health-care professionals.…”
Section: Introductionmentioning
confidence: 99%